Roma : the novel of ancient Rome - Saylor, Steven (New York : St. Martin's Press, 2007)
"Spanning a thousand years, and following the shifting fortunes of two families though the ages, this is the epic saga of Rome, the city and its people."--From source other than the Library of Congress